Antidepressant effects of Gardeniae Fructus on chronic unpredictable mild stress model mice: involvement of DNMT3B-mediated epigenetic regulation of GR in the prefrontal cortex - Lu-Lu Zhang; Xiao-Wei Wang; Yi-Dan Cheng; Ya Liu; Hesham R. El-Seedi; Peng-Cheng Sun; Wen-bin He; Jian-Jun Zhang; Zhi-Guang Zhai (Journal of Natural Medicines, 2026)

An adaptive multifidelity surrogates-based data assimilation approach for groundwater contamination sources identification - Xueman Yan; Lihe Yin; Jun Zhang; Yongkai An; Kun Yu; Wenxi Lu (Hydrogeology Journal, 2026)

Changes in vegetation cover based on fossil pollen data from Muricuo Lake on the eastern Tibetan Plateau since ∼6800 cal yr BP - Tao Wang; Xiaozhong Huang; Jun Zhang; Yao Ouyang; Lixiong Xiang; Chong Huang; Min Zheng (Science China Earth Sciences, 2026)

Microbial adaptations to stoichiometric imbalance mediate carbon release along an elevational gradient - Shujuan Guo; Lingge Zheng; Wenjun Zhang; Chao He; Sai Jia; Baogang Wang; Yadong Xu; Jinyong Huang (Applied Soil Ecology, 2026)

Intercropping enhances soil organic carbon accumulation by modulating microbial interactions in saline-alkali soils - Lijun Zhang; Guixiang Zhou; Jiabao Zhang; Lin Chen; Congzhi Zhang; Donghao Ma; Hui Zhang; Jian Feng; Mingfeng Liu (Applied Soil Ecology, 2026)

Soil moderately labile organic phosphorus as the most grazing-sensitive fraction in desert grasslands: Linking plant, soil, and microbial drivers - Qingge Zhao; Sylvie A. Quideau; Aimin Zhu; Yingzhong Xie; Yingjun Zhang; Ton Bisseling; Yunbo Wang; Guodong Han (Applied Soil Ecology, 2026)

Arbuscular mycorrhizal fungi mitigate microplastic-induced shifts in soil nematode communities - Jinghan Yue; Yuejiao He; Wenjing Ma; Cancan Zhao; Yinzhan Liu; Li Zhang; Guoyong Li; Yaojun Zhang (Applied Soil Ecology, 2026)

Interfacial microbial communities drive litter decomposition along elevation gradients in Segrila Mountain - Mengyao Dong; Wenzu Liu; Hongfang Ma; Ruihong Wang; Xinjun Zhang; Zhuonan Hou; Daqing Luo; Heping Ma; Bin Zhao; Yuquan Wei (Applied Soil Ecology, 2026)

Wind farm-induced redistribution of soil organic matter: Molecular insights into dissolved organic matter and microbial interactions - Qingyi Li; Jun Chen; Siwei Peng; Guozhu Zhang; Zexu Chen; Boyuan Yang; Yu Zhang; Siying Cai; Weijun Zhang (Applied Soil Ecology, 2025)

Intermittent oxygenation is essential for modulating nitrite ammonifiers in an agricultural upland soil to minimize nitrogen loss - Xiaogang Wu; Siyu Yu; Weikang Sui; Xinyu Zhang; Ji Li; Qiaoyu Wu; Xiaojun Zhang (Applied Soil Ecology, 2025)

Bradyrhizobial peanut inoculant competitiveness is associated with rhizosphere microbiota - Yue Wang; Yongju Xu; Lingzi Zhang; Ke Zhao; Xiaojun Zhang; Xiaohong Zhang; Petri Penttinen; Xiaoping Zhang (Applied Soil Ecology, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Effects of allelochemical 4-vinyl guaiacol and pathogen co-treatment on the physiological characteristics and soil microbial community structure in the Lanzhou lily - Zhanjun Zhang; Cuiping Hua; Yajun Wang; Yubao Zhang; Yang Qiu; Ruoyu Wang; Zhihong Guo; Zhongkui Xie (Applied Soil Ecology, 2025)

Single‐Cell Sequencing: A Sharp Sword for Deciphering Biological Innovations and Evolutionary Adaptations in Lower Vertebrates and Invertebrates - Chongbin Hu; Yun Hong; Lixin Xiang; Ye Chen; Jianzhong Shao; Hangjun Zhang (Reviews in Aquaculture, 2025)
Single‐cell sequencing (SCS) technology has revolutionized the study of cellular heterogeneity by enabling the exploration of biological processes at high resolution. While traditionally applied to mammalian models, recent advancements have extended SCS to ecologically and evolutionarily crucial lower vertebrates (particularly fish) and diverse invertebrates (including Urochordata, Echinodermata, Arthropoda, Mollusca, and Coelenterata). These non‐mammalian organisms exhibit unique cellular and molecular adaptations, serving as pivotal models for developmental biology, immune mechanisms, hematopoiesis, and environmental adaptation, yet remain underrepresented in genomics. This review highlights how SCS has been instrumental in uncovering novel cell types, defining intricate developmental trajectories, revealing unprecedented complexity in hematopoiesis, and elucidating diverse immune landscapes (including cell heterogeneity, functional specialization, pathogen responses, and tissue‐specific adaptations) in fish. Furthermore, it details the construction of foundational cell atlases across fish and invertebrate species and showcases SCS applications in mapping invertebrate development, characterizing cellular heterogeneity under varying conditions, and revealing unique environmental adaptations. Cross‐species SCS analyses provide powerful tools for tracing the evolution of critical systems, such as immunity. While addressing challenges like incomplete reference genomes and technical complexity, we discuss SCS's transformative potential in aquaculture and biotechnology, emphasizing future directions in multi‐omics integration and computational tool development to decipher biological innovations and evolutionary adaptations.

Effects of seed priming with different concentrations and forms of silicon on germination and growth of rice under cadmium stress - Yan Tan; Xin Liu; Zhibo Shen; Yang Xiao; Youjun Zhang; Huihui Du; Zhibin Wu; Dan Zhi; Avelino Núñez-Delgado; Yuan Yang (Applied Soil Ecology, 2025)

Differential impacts of lime and nitrogen amendment on nitrification, ammonia oxidizers, nitrite oxidizers, and bacterial communities in two acidic soils - Qing Wang; Yu Xin; Kun Yang; Suiliang Wang; Zhiyong Yu; Junfeng Qu; Yunze Ruan; Zhijun Zhang (Applied Soil Ecology, 2025)

Warming-induced response of microbial diversity and functions regulated microbial necromass and soil multifunctionality - Zhuonan Hou; Wenzu Liu; Shaoqi Xu; Su Chang; Xinjun Zhang; Ruihong Wang; Daqing Luo; Baorong Wang; Shaoshan An; Yuhui Qiao; Zhangliu Du; Yuquan Wei (Applied Soil Ecology, 2025)

Nitrogen deposition in the middle-aged and mature coniferous forest: Impacts on soil microbial community structure and function - Jun Zhang; Fei Yu; Zhaoyong Hu; Shouqin Sun; Xiangyang Sun; Juying Sun; Wei Zhang; Genxu Wang (Applied Soil Ecology, 2024)

Cover Image - Jianbo Yuan; Yang Yu; Xiaojun Zhang; Shihao Li; Jianhai Xiang; Fuhua Li (Reviews in Aquaculture, 2023)
The cover image is based on the Review Article Recent advances in crustacean genomics and their potential application in aquaculture by Jianbo Yuan et al., https://doi.org/10.1111/raq.12791 . image

Recent advances in crustacean genomics and their potential application in aquaculture - Jianbo Yuan; Yang Yu; Xiaojun Zhang; Shihao Li; Jianhai Xiang; Fuhua Li (Reviews in Aquaculture, 2023)
Genomic resources are increasingly being used to improve the production efficiency and profitability of aquaculture. Crustaceans are a large group of invertebrates that encompasses some of the most important farmed species in the aquaculture industry. However, very few crustacean genomes have been published although an aquaculture genome project was proposed as early as 1997. Breakthroughs in next‐generation and third‐generation sequencing technologies and the development of high‐complexity sequence assembly strategies have promoted the publication of an increasing number of crustacean genomes, thus paving a broad way for biological and genetic studies and applications in aquaculture. In this review, we summarize recent advances in crustacean genomic research as of June 2022, including genome sequencing and assembly, genomic characteristics, and the genetic mechanisms underlying various biological phenotypes, such as environmental adaptation, lifestyle, development, and sex determination. This review also discusses the application of crustacean genomes in aquaculture, including genetic dissection of economic traits and genome‐based selective breeding via genome‐wide association studies and genomic selection. High‐quality genomes are important not only for understanding the genetic basis of biologically and economically important traits but also for the genetic improvement of aquaculture species. However, the utilization of crustacean genomics still lags far behind those in other animals. Therefore, additional multi‐omics studies and technological development are needed to accelerate the application of genomics in aquaculture.